BADMINTON SMASH SKILL TRAINING MODEL FOR HIGH SCHOOL BEGINNERS STUDENTS - Dahniar Widya Puspita Dewi; Widiastuti; Samsudin (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study was to produce a product form of a badminton smash skill training model for high school beginners students (SMA) and to test the effectiveness of the developed training model. The author uses a development research design that adopts the development design of the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) by including high school athletes with the criteria and requirements for beginner athletes aged 14-17 years. At the model feasibility stage, 30 subjects were included to apply the model, 3 badminton experts were used as the validity of each model item, while at the effectiveness test stage 90 subjects were included. Data analysis was carried out descriptively qualitatively through documentation, interviews, and observations, while quantitative data to determine the difference in average skills was carried out using a paired sample test which was analyzed using SPSS-26. The correlation coefficient value is 0.331 with a significance value of 0.014, and the significance of the difference in t-count shows = -21.974, db = 43 and p-value = 0.00 < 0.05, meaning that there is a significant difference in athlete skills before and after being given the developed training model. It was concluded that the model could be developed and applied in practicing badminton smash skills; and a model that is made effective to improve the smash skills of beginner athletes at the high school level.